Operationalising energy sufficiency for low-carbon built environments in urbanising India - Ashok B. Lall; Girisha Sethi (Buildings & Cities)
India’s urbanisation is considered the largest national urban transformation of the 21st century, with its trajectory having a decisive impact on carbon emissions globally. This study defines and operationalises the concept of energy sufficiency for the growth of Indian cities which is expected to be largely driven by low- and middle-income housing. It combines theoretical framing with quantitative assessment of test models to present an operational framework of energy sufficiency that can be implemented through urban planning regulations. Based on the global budgetary limit to restrict global warming to 1.5°C, a precautionary target of 1.0 tCO2 per capita per year is estimated as an energy sufficiency allowance for upcoming residential built environments. By optimising the average dwelling size, limiting the land-use intensity to low-rise (four storeys) and compact urban forms, and improving operational energy performance with adaptive thermal comfort, the carbon emissions from residential buildings can be sufficiently optimised to 0.84 tCO2 per capita per year. The integration of rooftop renewable energy can further reduce it to 0.56 tCO2. The co-benefits of the optimised costs of construction and operation make the case for economic feasibility and wider affordability. Policy relevance The rapid urbanisation in India will significantly increase carbon emissions from the urban built environment. Current trends towards high-rise and high-density residential development contribute significantly to the demand for embodied and operational energy. However, these remain unaccounted for in India’s action plan to meet its nationally determined contribution (NDC) to reduce emissions intensity. Energy sufficiency can be used as a guiding principle for urbanising contexts to limit both the embodied energy of new residential buildings and the associated operational energy demands. The proposed framework for sufficiency serves as a useful policy instrument, capable of being translated to actionable urban planning regulations. By demonstrating the potential of a ‘sufficient’ per capita carbon emissions budget for the growth and regeneration of residential buildings, this framework equips planners to set limits for the height and density of the built environment, fostering a low-carbon future aligned with the United Nations’ Sustainable Development Goals (SDGs).